-2=-7(4a+7)

Simple and best practice solution for -2=-7(4a+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=-7(4a+7) equation:


Simplifying
-2 = -7(4a + 7)

Reorder the terms:
-2 = -7(7 + 4a)
-2 = (7 * -7 + 4a * -7)
-2 = (-49 + -28a)

Solving
-2 = -49 + -28a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '28a' to each side of the equation.
-2 + 28a = -49 + -28a + 28a

Combine like terms: -28a + 28a = 0
-2 + 28a = -49 + 0
-2 + 28a = -49

Add '2' to each side of the equation.
-2 + 2 + 28a = -49 + 2

Combine like terms: -2 + 2 = 0
0 + 28a = -49 + 2
28a = -49 + 2

Combine like terms: -49 + 2 = -47
28a = -47

Divide each side by '28'.
a = -1.678571429

Simplifying
a = -1.678571429

See similar equations:

| 3(2+5x)=-39 | | 6(8k+8)=0 | | 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 | | 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 | | 10x-26=264 | | 3x-8x= | | 21b^2-114b-72=0 | | 87=5n-23 | | .12(18)+0.03x=0.06(24+x) | | 10x=264 | | 37=x+48 | | 18m^2-77m-18=0 | | 3(0)=-y+3 |

Equations solver categories